2022
DOI: 10.1007/s00276-022-02960-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent trigeminal artery detected on computed tomography angiography

Abstract: This study aimed to investigate the prevalence of persistent trigeminal arteries (PTAs) using computed tomography (CT) angiography, emphasize its major characteristics, and compare the ndings with those reported in the relevant literature. MethodsPatients who underwent cerebral CT angiography in our radiology clinic for any preliminary diagnosis between December 2013 and December 2020 were included in this retrospective study. The patients were reviewed in terms of their age, sex, and the presence of PTAs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…PTA generally occurs on one side and is a relatively rare angiographic variation, which usually originates from the cavernous and petrosal segments of the ICA and terminates in the basilar artery [ 3 , 5 ]. There is currently no unified classification for the PTA; however, the Saltzman classification is commonly used clinically [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTA generally occurs on one side and is a relatively rare angiographic variation, which usually originates from the cavernous and petrosal segments of the ICA and terminates in the basilar artery [ 3 , 5 ]. There is currently no unified classification for the PTA; however, the Saltzman classification is commonly used clinically [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis demonstrated that 42.5% of patients with PTA have poor basilar artery development, leading to reduced blood supply in the posterior circulation [ 5 ]. In this scenario, blood flow through the PTA was directed from the ICA toward the basilar artery, making PTA a potential embolic pathway and significantly increasing the risk of posterior circulation embolism and ischemic stroke [ 3 , 4 ]. Therefore, we believe that the basilar artery occlusion in this patient was most likely an acute embolism from the anterior circulation entering the basilar artery through the PTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral type is the usual type, and approximately 90% of PTAs are classi ed as this type [2,5,11]. Medialtype PTAs are rare; however, Deniz et al [1] recently reported that 3 of 7 PTAs were medial-type. The medial type runs in the pituitary fossa; thus, it is also called intrasellar PTA and is dangerous during transsphenoidal pituitary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several fetal anastomoses have been described between the carotid and vertebrobasilar circulations [1][2][3][4][5][6][7][8][9][10][11]. These anastomoses regress while the P1 segments develop, but they can occasionally persist in adult age [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%